Frost on sugarcane crop in Rio Brilhante – MS - Nascimento, Jackeline Matos do; Oliveira, Gedivaldo; Viana, Jean Carlo Frozza; Colombo, Lucinete Regina; Jesus, Maílson Vieira; Secretti, Mateus Luiz (Brazilian Journal of Production Engineering, 2023)
The municipality of Rio Brilhante, in the state of Mato Grosso do Sul, is the second largest sugarcane planted area in Brazil. The 2021/22 harvest showed a drop of 10.60%, mainly due to frost and drought. This work consisted of procedures to monitor the damage caused by frost in the months of June and July of 2021 in sugarcane crops. High-resolution satellite images were used, providing accurate spectral data for monitoring and estimating the sugarcane cultivation area affected by frost. To obtain this result, we used Normalized Difference Vegetation Index (NDVI) technology, which indicates vegetation growth activity and has a strong correlation with dry matter. The experiment was conducted on ten farms in the aforementioned municipality, before and after the frost. The variables evaluated were: bud mortality; lateral sprouting; insulation of internodes; and NDVI. The effect of the occurrence of frost on the crop that could be observed most frequently was the death of the apical bud. No significant damage was observed when isolating. The NDVI images were extremely important for carrying out this analysis.